The Tabernacle of Moses Refers to Jesus' Earthly Ministry - Rimon Jonas Simanjuntak; Janes Sinaga; Juita Lusiana Sinambela (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is so that every Christian has a correct understanding of service in the heavenly Temple, which is the foundation of the Christian faith. So that every Christian is obliged to have a theological understanding of the understanding of the sanctuary and its ministry. This research method uses a qualitative method of literature review. Having an understanding of the temple makes a complete foundation of belief that must be studied and believed. The tabernacle is a symbol of God's presence in the midst of His people the Israelites, and is the center of the worship system. The tabernacle built by Moses, was built according to the pattern or pattern in heaven. The temple that Moses built in the desert, proves God's longing to remain silent among His people. The Temple is the real proof of God's presence with His people on earth.